Multifunctional cement-based materials modified with electrostatic self-assembled CNT/TiO2 composite filler. (30th March 2020) - Zhang, Liqing; Li, Linwei; Wang, Yanlei; Yu, Xun; Han, Baoguo
Highlights: Electrostatic self-assembled CNT/TiO2 composite fillers were used to fabricate multifunctional cement-based materials. Synergistic modifying effects of CNT and TiO2 endow cement-based materials with excellent multifunctional properties. Micro-scale TiO2 functions as a good filler for modifying cement-based materials and dispersing CNT. Abstract: Owing to its good conductive property, dispersion, and low water absorption property, the electrostatic self-assembled CNT/TiO2 composite filler is an excellent candidate for developing multifunctional cement-based materials. Therefore, this study fabricated multifunctional cement-based materials with a CNT/TiO2 composite filler and explored their electrical properties, thermal-resistance effect, electromagnetic shielding and absorption properties. CNT/TiO2 modified cement-based materials showed percolation characteristics through direct current (DC), alternating current (AC) resistivity methods and percolation theory, with percolation threshold zone ranging from 0.15 vol% to 0.45 vol%. The AC impedance spectrum of the CNT/TiO2 modified cement-based materials can be accurately described by equivalent circuits, which change in the percolation threshold zone. The resistivity of the CNT/TiO2 modified cement-based materials decreased with increasing temperature, which has potential application in smart infrastructures. With increasing CNT/TiO2, the rate of decrease of the electrical resistivity of the composites changed sharply during the percolation threshold zone for increasing temperature from −30 °C to 60 °C. The electromagnetic shielding effectiveness of CNT/TiO2 modified cement-based materials was up to 1.30 times greater than that of the control cement-based materials. When the CNT content was 1.16 vol%, the reflectivity of the cement-based composite reached −32.01 dB at a frequency of 16.88 GHz.